2018
DOI: 10.1016/j.renene.2018.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Pumps as turbines for efficient energy recovery in water supply networks

Abstract: a b s t r a c tThe present work aims to enhance the energy efficiency of water supply networks by investigating technical and economical feasibility of energy recovery plants at low installed capacities. A cost effective stainless steel machine is investigated in pump and turbine operation and established conversion methods are used for predicting the best efficiency point of the turbine. The obtained results show a reasonable agreement of the BEP, but experimental investigations are still indispensable for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 12 publications
(14 reference statements)
0
18
0
1
Order By: Relevance
“…experimental techniques to predict PAT performance from pump characteristics. Kramer et al concluded their study by saying that experimental investigations are still indispensable when an exact knowledge of turbine characteristics is required [28]. This issue is also addressed by Frosina et al [29] who proved by experimental verification that some methods (e.g., Childs' method) differ significantly from reality, while others (e.g., Stepanoff's method) show small relative differences.…”
Section: Volute Casing Nq = 25÷220mentioning
confidence: 99%
“…experimental techniques to predict PAT performance from pump characteristics. Kramer et al concluded their study by saying that experimental investigations are still indispensable when an exact knowledge of turbine characteristics is required [28]. This issue is also addressed by Frosina et al [29] who proved by experimental verification that some methods (e.g., Childs' method) differ significantly from reality, while others (e.g., Stepanoff's method) show small relative differences.…”
Section: Volute Casing Nq = 25÷220mentioning
confidence: 99%
“…In order to evaluate more accurately the cost of such plants, data from 9 energy recovery schemes in water networks from different countries have been compiled [24,[55][56][57]. All of the selected plants adopted a PAT as a generating device, and had nominal powers ranging from 9 to 120 kW.…”
Section: Prv Total Installation Costsmentioning
confidence: 99%
“…The use of PaTs as energy-recovery units has mainly been applied in WDNs [25]. WDNs constitute typical case studies where the control of pressure inside network branches through PRVs is crucial, as previously reported [26][27][28][29][30]. De Marchis et al [31] developed a dynamic mathematical model for intermittent WDNs in the city of Palermo located in Sicily (Italy): they integrated PaTs in the model and demonstrated their effectiveness to recover energy that would otherwise be wasted.…”
Section: Introductionmentioning
confidence: 99%